The intersection of harm reduction and postoperative care for an illicit fentanyl consumer after major surgery: A case report - Salima S. J. Ladak; Gonzalo Sapisochin; P. Maxwell Slepian; Hance Clarke (Taylor & Francis Group, 2021)
Background As Canada continues to address challenges related to the opioid crisis, individuals suffering from opioid use disorder (OUD) can be especially vulnerable to physical and psychological destabilization after surgery. Adopting a harm reduction approach postoperatively can be a success factor for safe recovery and satisfactory analgesia. Purpose We present the case of a 40-year-old patient (referred to as DC) with OUD using illicit fentanyl, heroin, and oxycodone preoperatively and admitted for an elective liver resection for steroid-induced hepatoma. Despite a preoperative anesthesia assessment and the initiation of a standard balanced multimodal analgesic regimen, suboptimal analgesia was evident in the first 24 h postoperatively. This lack of analgesic efficacy precipitated DC's use of illicit self-injected intravenous (IV) opioid and significant emotional distress. To address this, a nurse practitioner and anesthesiologist within the Toronto General Hospital acute and transitional pain program and the surgical team quickly met and adopted a harm reduction approach to manage DC's postoperative pain and emotional distress. The ultimate goal was to eliminate self-administration of illicit IV opioids and prevent DC from attempting to leave hospital against medical advice. Following an interprofessional team discussion that included DC, IV fentanyl was offered via a patient-controlled analgesia pump to DC's satisfaction (exceeding standard settings), providing acceptable pain relief. To our knowledge, DC did not self-administer additional illicit drugs during the remainder of hospitalization. Outcome This harm reduction approach resulted in DC's safe recovery, achievement of postoperative functional milestones, and continued engagement with outpatient pain treatment.